Structural and Hormonal Changes in Reproductive-Age Women Post-COVID-19: A Cross-Sectional Ultrasound and Biochemical Study - Sandugash Yerkenova; Vyacheslav Lokshin; Almagul Kurmanova; Sharapat Moiynbayeva; Galiya Alikeyeva; Gulnara Kalibekova; Tamara Abdirova; Zamira Zhantenova; Kuralay Shaikova; Alla Mireeva; Aknur Turgumbayeva (Diagnostics)
Background/Objectives: The long-term impact of COVID-19 on female reproductive health remains poorly understood. This study aimed to assess structural and endocrine alterations in women of reproductive age who had recovered from SARS-CoV-2 infection compared to uninfected controls. Materials and Methods: A total of 150 women aged 18–45 years were enrolled in a comparative study: 75 with a confirmed history of COVID-19 and 75 without one. All participants underwent ultrasound examinations of their pelvic organs and mammary glands, along with laboratory assessment of reproductive hormones and inflammatory markers. Results: Structural abnormalities in the pelvic organs were observed in 53.5% of the post-COVID-19 group versus 12.0% of the control group (p < 0.001), with oophoritis showing a statistically significant association (OR = 11.38; 95% CI: 1.42–91.36; p = 0.009). Non-significant but elevated frequencies were also found for uterine fibroids and breast cysts. Biochemically, post-COVID-19 participants demonstrated higher serum ferritin, estradiol, and fibrinogen levels, along with lower TSH and AMH levels, suggesting potential endocrine disruption and persistent inflammation. Conclusions: Women with a history of COVID-19 may be at increased risk of developing structural and hormonal abnormalities, highlighting the importance of post-infection gynecological and endocrine monitoring. Further longitudinal studies are required to elucidate the long-term effects and underlying mechanisms of these alterations.